Therapy Combining Glucagon-Like Peptide-1 Receptor Agonist with Sodium-Glucose Cotransporter 2 Inhibitor Suppresses Atherosclerosis in Diabetic ApoE-Deficient Mice - Takubo, Masahiro; Watanabe, Kentaro; Saito, Hitoki; Kohno, Genta; Ishihara, Hisamitsu (Experimental and Clinical Endocrinology & Diabetes, 2024)
Background Glucagon-like peptide-1 receptor agonists (GLP-1RAs) and sodium-glucose cotransporter 2 inhibitors (SGLT2i) have beneficial effects on cardiovascular disease in addition to their glucose-lowering effects. In this study, the effects of these drugs, when used individually or in combination, on cardiovascular atherosclerotic lesion development were compared in diabetic ApoE-deficient (ApoE KO) hyperlipidemic mice.Methods ApoE-KO mice were treated with streptozotocin and nicotinamide, generating a type 2 diabetes model. The mice were randomly divided into four groups: vehicle-treated (untreated), liraglutide (LIRA), ipragliflozin (IPRA), and combination therapy (combo). These mice, as well as non-diabetic controls, were fed a high-fat diet. After 8 weeks of drug administration, the heart and aorta were removed and analyzed.Results Atherosclerotic lesions evaluated by oil red O (ORO) staining were significantly larger in the untreated group (13.4±0.8% of the total aortic area) than in the non-diabetic controls (4.4±0.5%, p<0.01), while being reduced in the combo group (6.0±1.0%, p<0.01) as compared with the untreated group. The ORO stain-positive area in the LIRA and IPRA groups tended to be reduced but their differences were not statistically significant. Transcript levels of Mcp1 and Sirt1 were significantly reduced and increased, respectively, in the combo compared with the untreated group, while no significant changes were observed in the monotherapy groups.Conclusions The data suggest that combination therapy with liraglutide and ipragliflozin may be an efficient regimen for preventing the development of atherosclerosis in diabetic mice deficient in ApoE.
Keywords: atherosclerosis; SGLT2i; GLP-1RA